1993
DOI: 10.1093/infdis/168.1.219
|View full text |Cite
|
Sign up to set email alerts
|

The Cohort Effect and Helicobacter pylori

Abstract: A total of 631 serum samples collected in 1969, 1979, and 1989 from adults and children were screened for Helicobacter pylori by Western blot analysis. Results showed that H. pylori seroprevalence has become less frequent over the 20-year period. By studying seropositivity by year of birth, the magnitude of a cohort effect of H. pylori seropositivity was estimated. The odds of being seropositive decreased by 26% per decade, P = .008 (95% confidence interval, 8%-41%). Estimates of seroprevalence adjusted for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
247
2
15

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(288 citation statements)
references
References 8 publications
23
247
2
15
Order By: Relevance
“…A similar finding was reported from studies done in developing countries (Moges et al, 2006;Tanih et al, 2010;Ameri et al, 2013). This increase in prevalence with age is attributed to annual increase in the rate of infection (Goodman et al, 1996) and birth cohort effect (Banatvala et al,1993 Alvarado-Esquivel, 2013;Dirji et al, 2013). On the other hand, Alizadeh et al (2009) reported that the prevalence of H. pylori was higher in females than males, while Valliani et al (2013) found out that the prevalence was higher in males than females.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported from studies done in developing countries (Moges et al, 2006;Tanih et al, 2010;Ameri et al, 2013). This increase in prevalence with age is attributed to annual increase in the rate of infection (Goodman et al, 1996) and birth cohort effect (Banatvala et al,1993 Alvarado-Esquivel, 2013;Dirji et al, 2013). On the other hand, Alizadeh et al (2009) reported that the prevalence of H. pylori was higher in females than males, while Valliani et al (2013) found out that the prevalence was higher in males than females.…”
Section: Discussionmentioning
confidence: 99%
“…H pylori is a known risk factor for the development of gastritis and IM. Worldwide, the incidence of gastric cancer is declining, most likely due to the decrease of infection by H pylori (31,32). An opposite trend is seen in the cardia, with increasing incidence of cardiac adenocarcinoma, despite decreasing H pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,94,104,116 Entretanto, nos países em desenvolvimento, a prevalência da infecção é mais alta em todas as faixas etárias. Essa diferença é mais acentuada na infância, como pode ser observada nas Figuras 1 e 2.…”
Section: Prevalência Relacionada à Idadeunclassified